2022
DOI: 10.1186/s12959-022-00432-9
|View full text |Cite
|
Sign up to set email alerts
|

Standard dosing of enoxaparin versus unfractionated heparin in critically ill patient with COVID-19: a multicenter propensity-score matched study

Abstract: Background Thrombotic events are common in critically ill patients with COVID-19 and have been linked with COVID-19- induced hyperinflammatory state. In addition to anticoagulant effects, heparin and its derivatives have various anti-inflammatory and immunomodulatory properties that may affect patient outcomes. This study compared the effectiveness and safety of prophylactic standard-doses of enoxaparin and unfractionated heparin (UFH) in critically ill patients with COVID-19.  … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 38 publications
1
0
0
Order By: Relevance
“…This study was carried out under the auspices of the Saudi Critical Care Pharmacy Research (SCAPE) platform, which also conducted other investigations to evaluate the safety and effectiveness of various therapies in critically ill patients ( SCAPE, n.d. ). The methodology of this multicenter cohort study is comparable to other studies executed by the SCAPE platform and previously reported ( Al Harbi et al, 2022 , Al Sulaiman et al, 2022b , Al Sulaiman et al, 2022a , Al Sulaiman et al, 2021a , Al Sulaiman et al, 2021b , Aljuhani et al, 2021 ). The supplemental material contains additional details on the study's design.…”
Section: Methodssupporting
confidence: 59%
“…This study was carried out under the auspices of the Saudi Critical Care Pharmacy Research (SCAPE) platform, which also conducted other investigations to evaluate the safety and effectiveness of various therapies in critically ill patients ( SCAPE, n.d. ). The methodology of this multicenter cohort study is comparable to other studies executed by the SCAPE platform and previously reported ( Al Harbi et al, 2022 , Al Sulaiman et al, 2022b , Al Sulaiman et al, 2022a , Al Sulaiman et al, 2021a , Al Sulaiman et al, 2021b , Aljuhani et al, 2021 ). The supplemental material contains additional details on the study's design.…”
Section: Methodssupporting
confidence: 59%